Dépôt de polluants sur les espaces agricoles à proximité des voies de transport en Île-de-France - Caroline Petit; Benjamin Loubet; Elisabeth Rémy; Christine Aubry; Fabrice Duguay; Julie Missonnier; Pierre Cellier; Amir Ali Feiz; Cécile Blondeau; Cécile Mauclair; Brigitte Durand (VertigO)
The project “Local Pollution, Transport and Agriculture” (PPTA) aimed at evaluating the deposition of pollutants onto agricultural areas emanating from traffic lines in the Parisian area, and at evaluating how the risk was perceived by farmers and consumers. The project was split in three parts: (1) Quantification of the pollutant deposition near traffic lines; (2) Analysis of how the farmers, consumers, side residents, and actors of the food supply chains perceived this pollution and its risks and eventually how they adapt to them; and (3) Analysis of the agricultural surfaces potentially impacted by this local pollution in the Île-de-France region and a review of the possible road planning options to reduce these potential impacts. The project was centred on the notion of “guard distance” or “impact distance” and a special attention was paid on the physical terms and social drivers defining this term. The first part of the project showed that the concentrations of nitrogen oxides (NOx), particulate mater below 2.5 µm diameter (PM2.5) and and 10 µm diameter (PM10) were lower near the A6 subway than on areas of high traffic in Île-de-France region. Comparison of models showed similar results in terms of pollutant concentrations but significant differences in terms of deposition rates. The second part of the project aimed at understanding perception and adaptation of three main categories of actors about air pollution due to road traffic: while some actors of food supply chains explicitly take into account this issue by implementing technical guidelines, farmers and environmental groups do not consider road traffic pollutant deposition onto their fields as an issue. The third part of the project shows that a significant fraction of the farmland would be impacted by protective recommendations and that specific protection arrangements would be difficult to implement due to costs and effectiveness issues.The article describes the implementation of this multidisciplinary project, discusses its major results and proposes perspectives for further understanding the relationship between road traffic, air pollution and agricultural areas.